Securing cyberspace : whose responsibility? - Senol Yilmaz (2014)
Besides the ongoing vandalism by Anonymous on websites in Southeast Asia and beyond, cyberattacks can pose serious threats to national security particularly when critical infrastructure is targeted. There is need for private-public partnership to secure cyberspace.